Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.